2002
DOI: 10.1186/1471-2156-3-40
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcription map of the wobbler critical region on mouse chromosome 11 and the homologous region on human chromosome 2p13-14

Abstract: Background: To support the positional cloning of the mouse mutation wobbler (wr) the corresponding regions on human Chr2p13-14 and mouse Chr11 were analyzed in detail and compared with respect to gene content, order, and orientation. Results: The gene content of the investigated regions was highly conserved between the two species: 20 orthologous genes were identified on our BAC/YAC contig comprising 4.5 Mb between REL/Rel and RAB1A/Rab1a. Exceptions were pseudogenes ELP and PX19 whose mouse counterparts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Increasingly from 3 weeks of age, wobbler mice can be identified by their smaller size, a low frequency tremor that causes the head to wobble and weakness of the forelimbs. They are homozygote for an unidentified recessive mutant gene that maps to an identified region of chromosome 11 [22]. All animals were killed by transcardiac perfusion with buffered 4% paraformaldehyde solution (50 ml) following a brief perfusion with saline whilst under deep sodium pentobarbitone‐induced anaesthesia, according to procedures approved by the local Ethical Review Committee and licensed by the UK government Home Office.…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly from 3 weeks of age, wobbler mice can be identified by their smaller size, a low frequency tremor that causes the head to wobble and weakness of the forelimbs. They are homozygote for an unidentified recessive mutant gene that maps to an identified region of chromosome 11 [22]. All animals were killed by transcardiac perfusion with buffered 4% paraformaldehyde solution (50 ml) following a brief perfusion with saline whilst under deep sodium pentobarbitone‐induced anaesthesia, according to procedures approved by the local Ethical Review Committee and licensed by the UK government Home Office.…”
Section: Methodsmentioning
confidence: 99%
“…The chromosomal mapping of the wobbler locus revealed that the disease-causing gene was autosomal, recessive, and presumably unique. The wobbler gene was found in proximal mouse chromosome 11 [ 80 , 81 ], which is homologous to human chromosome 2p13-14 [ 82 ]. This mutation was identified using positional cloning as a point mutation in the final exon of the VPS54 gene.…”
Section: Garp Complex Mutations and Pathogenesismentioning
confidence: 99%